Impact of early (<7 days) pacemaker implantation after cardiac surgery on long‐term pacemaker dependency. Issue 6 (24th May 2021) - Badoz, Marc; Favoulet, Baptiste; Serzian, Guillaume; Ecarnot, Fiona; Guillon, Benoit; Chopard, Romain; Meneveau, Nicolas
Abstract: Objective: We aimed to investigate pacemaker dependency after at least 1 year in patients with early (<7 days) implantation, compared to those who received a pacemaker ≥7 days after cardiac surgery. Secondary endpoints were length of hospital stay and in‐hospital complications. Methods: Retrospective analysis of 108 consecutive patients who received a pacemaker after cardiac surgery between 06/2012 and 06/2018. Characteristics and outcomes were compared between patients with early (<7 days) and late (≥7 days) implantation. Patients were followed up with evaluation of pacemaker dependency between April and June 2019. We identified predictors of dependency by logistic regression. Results: In total, 63.9% were men, average age 71.9 ± 11.8 years; 32 (29.6%) had early implantation, and 76 (70.4%) late implantation. After a median 3.2 years [IQR 1.9, 4.5] of follow‐up, 30 patients (27.8%) had died, and there was no difference in pacemaker dependency among survivors (66.7% vs. 46.5%, early vs. late respectively, p  = .15). Patients in the early group had a shorter length of stay (11.5 [9.0, 14.0] vs. 15.0 [11.5, 20] days, p  = .002) and less often had new‐onset atrial fibrillation (AF) post‐surgery (22.7% vs. 47.8%, p  = .05). The only significant predictor of dependency was aortic valve replacement surgery (OR = 4.70, 95% CI [1.36 to 16.24]). Conclusion: Early implantation of a permanent pacemaker (<7 days after cardiac surgery) does not impact on the proportion of patients with long‐term (>12 months) pacemaker dependency, but is associated with shorter length of stay and less frequent new‐onset AF. These findings warrant prospective confirmation in randomized trials.